GENETIC VARIATION IN HOST IMMUNE RESPONSE TO MAJOR INFECTIOUS DISEASES IN BOVINES AND ITS APPLICATION IN ANIMAL BREEDING : A REVIEW - Chhaya Rani; Anuj Chauhan; Indrasen Chauhan; Sakshi Vaishnav; Argana Ajay; Tapendra Saini; Snehasmita Panda; G. K Gaur; Bharat Bhushan (Exploratory Animal and Medical Research, 2023)
Livestock infectious diseases pose a significant threat to animal health and welfare on a worldwide scale, and efficient management of these diseases is essential for maintaining agronomic health, securing national and international food supply, and reducing rural poverty in developing nations. It is challenging to eliminate the negative effects of disease effectively, economically, and permanently in livestock because of the shortcomings and constraints of current non-selection disease management approaches (e.g., vaccination, treatment, eradication strategy, and genome editing). Due to these shortcomings and restrictions, breeders are more interested and committed to addressing livestock health issues by selecting animals with favorable health traits. Selecting animals with specific health traits (such as disease tolerance, disease resistance, and immune response) can help to improve the health of livestock. Variability in host immune responses to infection plays a major role in host genetic variation in disease resistance. An approach can be employed as a strategy to fight infections by finding animals that are relatively immune or tolerant to diseases and revealing the inherent genetic variations in immune response at the molecular level. The accelerated and expanding understanding of genes and genomes in livestock, such as the evaluation of a broad number of DNA markers in phenotypic registered populations, could be used to identify and classify candidate genes responsible for variation in the immune response against major infectious diseases which would undoubtedly improve animal selection processes. Advancements in marker research could influence the selection programs if incorporated with the herd's genetic variant details as well as production traits. In this review, we have highlighted the genetic variation observed in host immune response to infectious diseases in bovines and its use in animal breeding for disease resistance.